Family Influences on the Dental Caries Status of Children with Special Health Care Needs: A Systematic Review - Diyana Shereen Anwar; Mohd Yusmiaidil Putera Mohd Yusof; Mas Suryalis Ahmad; Budi Aslinie Md Sabri (MDPI AG, 2022)
Oral health is a likely source of health inequalities in children with special health care needs (CSHCN), according to multiple studies. This systematic review aimed to explore the evidence of family influence-as well as family features, such as societal variables and parents' perspectives-on these children's dental caries status. Embase, Ebsco, Scopus, PubMed, and Web of Science databases were all searched. All cross-sectional research published on the variables of family impact ranging from 2010 to 2021 were considered. The DMFT and dmft index was utilised for the report data of dental caries, whereas the National Heart, Lung, and Blood Institute (NHLBI) was used for the purposes of assessing quality. Of the 3861 records identified, 14 were eligible. Further, most of the studies had a caries prevalence of over 50%, (p-value < 0.005). Family influences imparted a significant relationship and association towards the dental caries status of the demographic being studied. The influences on the children included tooth brushing behaviour, parents' education level, parents' occupation level, diet pattern, dental visit, snacking frequency, parents' psychological status, family size, and parents' knowledge towards oral health. Future research should further explore the family functioning domains, specifically among the CSHCN population. This study was registered on PROSPERO, number CRD42021274923.